Unveiling an Unanticipated Cause of Pulmonary Hypertension: Partial Anomalous Pulmonary Venous Connection in a Hypersensitivity Pneumonitis Patient - Garg , Shivam; Upadhya , Pratap; Jeevanandham , A.; Rao , Harshith (Current Progress in Medicine and Medical Research Vol. 6, 2023)
This chapter describes a case of non-fibrotic Hypersensitivity Pneumonitis (HP), suspected to have hypoxia-related Class III pulmonary hypertension, which on further evaluation, was found to have PAPVC-causing PAH. Any pulmonary vein, but not all of them, can drain into the right atrium or one of its venous tributaries directly, leading to a condition known as partial anomalous pulmonary venous connection (PAPVC). Rarely can PAPVC be the only factor contributing to pulmonary arterial hypertension. However, the occurrence and clinical significance of PAPVC as a cause of pulmonary artery hypertension in patients with hypersensitivity pneumonitis has never been documented. A 41-year-old male farmer presented with exertional dyspnoea - Modified Medical Research Council (mMRC) functional class II, and dry cough for 3 years, exacerbated over six months (mMRC class IV). Chest High-Resolution Computed Tomography (HRCT) was suggestive of non-fibrotic hypersensitivity pneumonitis. In our patient, based on his occupational history, clinical presentation, HRCT findings, and BAL reports, a diagnosis of non-fibrotic HP was made. Hence the patient was started on systemic steroids, with which the patient’s oxygen saturation improved. Still, as moderate PH was unexplained, he was evaluated further, leading to the recognition of PAPVC-associated PAH. On 2D-ECHO, the right ventricle systolic pressure was 48+RAP. Right heart catheterisation showed mean pulmonary artery pressure of 73 mmHG, PVR 8.7. The left superior pulmonary vein was found to leak into the left brachiocephalic vein during the subsequent investigation with CTPA.